Jinn And Mental Ilness Among Muslims - A Commentary - Md Rosli AN; Hashi AA; Razali ZA (Kulliyyah of Medicine, International Islamic University, 2024)
Vol. 19 No. 1 (2020): IIUM Medical Journal Malaysia - April 2020